Validation of National Early Warning Score and Quick Sequential (sepsis‐related) Organ Failure Assessment in acute myeloid leukaemia patients treated with intensive chemotherapy. (24th March 2023) - Frairia, Chiara; Nicolino, Barbara; Secreto, Carolina; Messa, Emanuela; Arrigo, Giulia; Busca, Alessandro; Cerrano, Marco; D'Ardìa, Stefano; Dellacasa, Chiara; Evangelista, Andrea; Freilone, Roberto; Giai, Valentina; et al.
Abstract: Objectives: Chemotherapy‐induced neutropenia in acute myeloid leukaemia (AML) is a risk factor for life‐threatening infections. Early diagnosis and prompt interventions are associated with better outcomes, but the prediction of infection severity remains an open question. Recently, National Early Warning Score (NEWS) and quick sequential organ failure assessment (qSOFA) scores were proposed as warning clinical instruments predicting in‐hospital mortality, but their role in the haematological context is still unknown. Methods: We retrospectively assess the predictive role of NEWS and qSOFA in a large and homogeneous cohort of adult AML patients treated with intensive chemotherapy. In a total of 1048 neutropenic episodes recorded in 334 consecutive patients, the scores were applied to predict outcomes on the same day of fever onset, and after 24 and 48 h from score calculation. Results: Both NEWS and qSOFA significantly predicted death, with more accuracy on the same day (NEWS AUROC 0.984 and qSOFA AUROC 0.969) and after 24 h (NEWS AUROC 0.928 and qSOFA AUROC 0.887), while remained moderately accurate after 48 h. Furthermore, also ICU admission was accurately predicted at fever onset and after 24 h. Conclusions: Both scores were useful tools in the management of post chemotherapy neutropenic febrile AML patients.